EFFECTS THAT DRIVE CUSTOMERS TO FAR EASTERN RESTAURANTS AND PERCEPTIONS OF COVID-19 (Third Sector Social Economic Review, 2021)
In this study, it is aimed to determine under which effects customers visit Far Eastern restaurants and how these customers' perceptions of Far Eastern restaurants have changed due to COVID-19. Qualitative design approach was used in the study. Seventeen participants who visited the Chinese, Japanese and Thai restaurants were selected as the sample. A semi-structured interview questionnaire was prepared based on literatüre and purpose of the research. The data were collected with the in-depth interview technique. Content analysis and descriptive-interpretative analysis were used in the analysis of the data. Factors driving the participants to the Far East restaurant is determined as personal effects; hedonic effect, interpersonal effects; bandwagon effect, snob effect, prestige effect and functional effects; health effect, chef effect. In addition, the concern that the content of Far Eastern dishes may cause viruses created a negative thought in some of the participants. The majority of participants do not have any negative thought for these restaurants. In particular, they lean to Far East restaurants in Turkey. First of all, the study will ensure the recognition of the profile of Far Eastern restaurant customers, especially in terms of personal, interpersonal and functional values. The emergence of the perception of Far Eastern restaurants during the pandemic process will enable businesses to develop a strategy for the crisis. First of all, businesses can develop the right marketing strategies to break the negative perception of Far East restaurants. This study offers clues to policy-makers for the destruction of the negative perceptions of Far East countries. Also This study is the first attempt in the literature to determine the effects that drive customers to Far Eastern restaurants and to determine their perspective towards these restaurants during the COVID-19 process.
Keywords: Far Eastern Restaurants; Personal Effects; Interpersonal Effects; Functional Effects; COVID-19.